The perceptions and practices of pregnant women towards prevention of mother-to-child transmission of HIV and AIDS in the Capricorn District, Limpopo Province, South Africa - Malema, R. N.; Mothiba, N. S.; Maputle, M. S. (My University, 2014)
Despite the fact that testing for HIV is voluntary and free of charge in public health centres, the majority of people including pregnant women are still reluctant to be tested. Many people are ignorant of their HIV status. The purpose of this study was to explore the perceptions and practices of pregnant women towards prevention of mother-to-child transmission of Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome (HIV and AIDS). A quantitative study applying the cross-sectional design was conducted in the 14 clinics of the Capricorn District of the Polokwane municipality in the Limpopo province, South Africa. A random sample of 73 pregnant women who were seeking antenatal care for the first time were selected and interviewed. The age group of 20-24 years had the highest pregnancy rate of 39% followed by teenagers aged 15-19 years (27%). Three–quarters (74%) of the pregnant women were learners and 68% of them were willing to take the HIV test. Those who were unwilling to take the test cited various fears, 78% knew about mother-to-child transmission (MTCT) of HIV and AIDS and 53% did not know how it occurs. Over a year 3948 pregnant women were counselled and 79% accepted to be tested; out of which 16% tested HIV-positive. It is recommended that awareness campaigns about MTCT prevention of HIV be intensified even amongst students as young as 12 years. More resources are needed to deal with the stigma still attached to being HIV-positive. Keywords: Perceptions, practices, prevention
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:1 (June), 2014, pp. 40-57.
Keywords: HIV/AIDS transmissions; Mother-to-child transmissions; HIV/AIDS perceptions; AIDS (Diseases) -- South Africa